Early Detection of ARI Disease and First Aid in Children with Fever Seizures at Posyandu Cadres at Kantil Depok, Sleman - Sri - Handayani (Universitas 'Aisyiyah Yogyakarta, 2021)
Background: Acute Respiratory Infection (ARI) is one of the problems of death in children in developing countries. ARI is an upper or lower respiratory tract disease, usually contagious, which can cause a wide spectrum of disease that ranges from asymptomatic disease or mild infection to severe and deadly disease.Objective: Yandu cadres can improve knowledge, attitudes and skills in handling ARI and febrile seizures in children, so as to optimize growth and development in children optimally.Methods: socialization and simulation of the handling of ARI and febrile seizures in children through cadres. Cadres were given material about ARI and febrile seizures, followed by interactive activities about the steps taken to overcome/handle ARI and febrile seizures in children. The cadres were divided into three groups and accompanied by one trainer.Results: the cadres stated that they understood, and seemed capable of handling febrile seizures in children.Suggestion: The existence of counseling and training to parents/mothers about ARI and handling febrile seizures in children, providing first aid kits and simple medicines for handling febrile seizures at Posyandu, also in families who have children and often experience febrile seizures under the supervision of a doctor, it is necessary the existence of socialization in physical form contains the importance of handling febrile seizures in children.